Does accountability discharged through performance measurement system? - Ali, Amin; Elham, Faisol; Alauddin, Ahmadasri (Elsevier Ltd., 2014)
This paper discusses the relevant literatures with regard to the conceptualization of accountability from different perspectives, particularly from private and public sector.The importance of discharging accountability and related problems are also discussed in the paper.The next section of the paper deals with the linkages between accountability and performance measurement system comprising the issues of using performance measurement in the public sector and other implementation issues.The discussion of these issues is then relates to the philosophy of new public management (NPM) being adopted by public sector.The conflicting results on the roles of NPM in enhancing effectiveness are also being articulated, blending together the human aspects and the cultural values as pre-requisites for the success.